(3CRgGQ GdCZUGf GdegUhQI ef QjGV CafGf GdebUhQIs - (3CHhMGeO GdMGL Gdecj Hf eMeO Hf Ydj Hf YHO GdQMef GdHWGhj GdTQja GdMSjfjs; (3,J (B807 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi bUQJ Yf EOQGc cfgI GdCagGe hGdfgi s
(3BNQgG (B:s
(3hCZaQ dfG hdhGdOjfG hdLejY GdeSdejf GdCMjGA efge hGdejJjf , hBNQ OYhGfG Gf GdMeO ddg QH GdYGdejf s
(3HChdgG agQSJs
(3hbO TQM HGdeNWhW ebUhQI GdechOj aj GdSjQI GdfHhjIs
(3EPGfkG dCeQ TjNg CHj ESMGb GHQGgje Hf eMeO GdTGPdis
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJGQjNs